Fraud Prevention of Village Funds - Andini Ningtyas Mufliza; Indira Januarti (PT Mattawang Mediatama Solution, 2023)
Village funds refer to the allocation of funds distributed to villages as part of the government's efforts to improve the development and welfare of people in rural areas. However, there is often misuse of village funds by village officials, which results in cases of corruption of village funds within the village government. The purpose of this study was to obtain empirical evidence on the impact of individual morality and whistleblowing on the prevention of village fund fraud. This research is a quantitative-oriented study that uses primary data in the form of questionnaires given to 122 village apparatuses in Muara Kemumu District. Data processing is carried out using Smart Partial Least Squares (PLS). The results of this study show that individual morality and whistleblowing have a positive impact on preventing village fund fraud